Eat it to beat it! : banish belly fat--and take back your health--while eating the brand-name foods you love! - Zinczenko, David (Ballantine Books Trade Paperbacks, 2013)
ABC News Nutrition and Wellness editor Dave Zinczenko, author of the multimillion-copy bestselling Eat This, Not That! series, blows the lid off the bizarre, unnecessary, and shocking ingredients in many common brands, and shows you how making smart choices about the foods you love -- including burgers, pizza, and chocolate -- can help you lose weight, drop blood pressure, boost your immune system, and more.